2013
DOI: 10.14260/jemds/374
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Assess Knowledge , Attitude and Practice of Adverse Drug Reaction Reporting Among Physicians in a Tertiary Care Hospital

Abstract: BACKGROUND: Adverse drug reaction (ADR) monitoring and reporting activity is in its infancy in India. Spontaneous reporting of adverse drug reactions (ADR) is an important method in pharmacovigilance, but under-reporting is a major limitation. AIMS: Physicians being frontline caregivers this study was conducted to assess the knowledge, attitude and practice (KAP) of ADR reporting among physicians in a tertiary care hospital. SETTING AND DESIGN: This cross sectional, questionnaire based study was carried out am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
(16 reference statements)
1
14
1
Order By: Relevance
“…This finding is consistent with another same study in which the participants revealed their willingness to learn and to improve their pharmacovigilance knowledge in order to improve ADR reporting [23].Education is known to serve as the leading factor to empowerment. In Malaysia, a study conducted by Elkalmi et al had shown the positive impact of educational intervention in improving the pharmacists' perception on pharmacovigilance [24].…”
Section: Results On Attitude Of Adr Reportingsupporting
confidence: 90%
See 4 more Smart Citations
“…This finding is consistent with another same study in which the participants revealed their willingness to learn and to improve their pharmacovigilance knowledge in order to improve ADR reporting [23].Education is known to serve as the leading factor to empowerment. In Malaysia, a study conducted by Elkalmi et al had shown the positive impact of educational intervention in improving the pharmacists' perception on pharmacovigilance [24].…”
Section: Results On Attitude Of Adr Reportingsupporting
confidence: 90%
“…An interesting finding in our study was almost all study participants agreed that ADR reporting should be made mandatory. This was found to be much higher as compared to other studies, where only 60% doctors, 40% of pharmacists and 53% of physicians agreed on the mandatory ADR reporting [18,23]. Despite the positive attitude of our study population towards ADR reporting, the reporting rate remains low.…”
Section: Results On Attitude Of Adr Reportingcontrasting
confidence: 76%
See 3 more Smart Citations